My New School: transition to high school for children with special educational needs in England – findings and ideas for practice. Issue 2 (17th June 2019) - Bunn, Helena; Boesley, Lauren
Abstract : While transition from primary to secondary school is an exhaustively researched area, there is limited research into how the ideas and insights of children, particularly those with Special Educational Needs (SEN), could inform or guide successful school transition planning. The current article presents the final stage of an action research project in which a transition intervention was designed by students in collaboration with their schools and educational psychology services. The intervention, 'My New School', was initially piloted in an inner‐city primary school in England (see Bunn, Davis and Speed 2017) and since has developed into a working tool for several other schools. Children's views, alongside those of school staff, were used to inform the final design of 'My New School' intervention. The article explores findings from analysing the participating children and school staff, alongside relevant literature, and final discussions and implications for practice conclude.